PENGEMBANGAN KARAKTER PADA SEKOLAH TINGGI KEDINASAN DALAM MENGHADAPI ERA SOCIETY 5.0 - Fanila Kasmita Kusuma (LPSDI Bina Patria, 2024)
The rapid development of information and communication technology brings drastic changes in society and the education industry. The key to achieving medium and long term growth is to realize Society 5.0 that solves various community challenges by incorporating every industry and social life 4th Industrial Revolution innovation (e.g., IoT, big data, AI, robotics, sharing economy and so on) which is growing rapidly. In the world of education, this technological development is also targeting higher education. So it is necessary to build character so that the use of this technological progress remains at its definition so that it has unity and healthy progress. The purpose of this This paper is to highlight the development of character education in official high schools in the midst of digital transformation in the 5.0 era. It seems that there is something that becomes the basis for being a part of changing the evolution and achievements of human society future human needs. To understand ICT skills and Digital competencies from a broader perspective and educational needs in order to prepare for Society 5.0.